Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1371/journal.pone.0036155
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Changes of the Human Macula during Acute Exposure to High Altitude

Abstract: BackgroundThis study aimed to quantify structural and functional changes at the macula during acute exposure to high altitude and to assess their structure/function relationship. This work is related to the Tuebingen High Altitude Ophthalmology (THAO) study.Methodology/Principal FindingsSpectral domain optical coherence tomography and microperimetry were used to quantify changes of central retinal structure and function in 14 healthy subjects during acute exposure to high altitude (4559 m). High-resolution vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
28
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 36 publications
2
28
0
Order By: Relevance
“…11,12 To minimize diurnal variation, all subjects (only right eyes) were assessed once a day at 9:00 AM, approximately 2 hours after awakening. All recordings were performed by the same investigator.…”
Section: Anterior Segment Optical Coherence Tomographymentioning
confidence: 99%
See 2 more Smart Citations
“…11,12 To minimize diurnal variation, all subjects (only right eyes) were assessed once a day at 9:00 AM, approximately 2 hours after awakening. All recordings were performed by the same investigator.…”
Section: Anterior Segment Optical Coherence Tomographymentioning
confidence: 99%
“…[7][8][9][10] However, measurements acquired any time after descent or in chambers may not necessarily reflect the changes during exposure to high altitude-related hypoxia. 7,11 These difficulties may account for some of the variability in results and conflicting conclusions drawn from those studies.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in mountaineers revealed that an ascent to high altitude may cause morphological and functional changes of the retina, such as optic disc swelling, changes of macular function including color discrimination, altered retinal and choroidal blood flow, and retinal hemorrhages (Frayser et al, 1970;Wiedman, 1975;Pavlidis et al, 2005;Morris et al, 2007;Bosch et al, 2008Bosch et al, , 2009Willmann et al, 2010Willmann et al, , 2011Ho et al, 2011;Fischer et al, 2012). While some of these changes present physiological adaptive mechanisms to high altitude exposure such as increased blood flow and increased tortuosity of blood vessels, others present potentially pathological changes to hypoxia, such as optic disc swelling or retinal hemorrhages.…”
Section: High Altitude-associated Changesmentioning
confidence: 99%
“…[1][2][3] As refractive surgery changes the properties of the cornea and the lens, concerns about refractive or intraocular lens (IOL) procedures in humans exposed to extreme situations have been raised.…”
mentioning
confidence: 99%